Advanced biological treatment processes - Wang, Lawrence K.; Shammas, Nazih K.; Hung, Yung-Tse (Humana Press, 2009)
Volume 9: Advanced Biological Treatment Processes in the Handbook of Environmental Engineering series provides critical insight into pollution-abatement engineering. This outstanding collection of methodologies is designed as a review of engineering systems currently being used, as well as their potential for use in pollution abatement. The book's expert panel of authors provides a look at a range of topics, including principles and kinetics of biological processes, vertical shaft bioreactors, upflow sludge blanket filtration, membrane bioreactors, column bioreactor, SBR, nitrification, denitrification, and emerging biological processes.